Efficient Cryopreservation of Porcine Blastocysts produced by In vitro Fertilization - Sung-Hun Min; Hak Jun Jeong; Deog-Bon Koo (The Korean Society of Animal Reproduction and Biotechnology, 2016)
Cryopreservation has been applied successfully in many mammalian species. Nevertheless, pig embryos, because of their greater susceptibility to cryoinjuries, have shown a reduced developmental competence. The aim of this study was to evaluate the survival status of vitrified-warmed porcine embryos. Forced blastocoele collapse (FBC) and non-FBC blastocysts are vitrified and concomitantly cultured in culture media which were supplemented with/without fetal bovine serum (FBS). Porcine vitrified-warmed embryos were examined in four different methods: group A, non-FBC without FBS; group B, non-FBC with FBS; group C, FBC without FBS; group D, FBC with FBS. After culture, differences in survival rates of blastocysts derived from vitrified-warmed porcine embryos were found in group A∼D (39.5 (A) vs 52.5 (B) and 54.8 (C) vs 66.7% (D), respectively, p<0.05). Reactive oxygen species (ROS) level of survived blastocysts was lower in group D than that of another groups (p<0.05). Moreover, total cell number of survived blastocysts was higher in group D than that of other groups (p<0.05). Otherwise, group D showed significantly lower number of apoptotic cells than other groups (2.0±1.5 vs 3.2±2.1, 2.8±1.9, and 2.7±1.6, respectively, p<0.05). Taken together, these results showed that FBS/FBC improves the developmental competence of vitrified porcine embryos by modulating intracellular levels of ROS and the apoptotic index during the vitrification/warming procedure. Therefore, we suggest that FBS and FBC are effective treatment techniques during the vitrification/warming procedures of porcine blastocysts.